2022
DOI: 10.3390/agronomy12071588
|View full text |Cite
|
Sign up to set email alerts
|

Differentially Expressed Transcription Factors during Male and Female Cone Development in Pinus halepensis

Abstract: The molecular regulation of induction and development of reproductive organs is well established in angiosperms, while it is slowly accumulating in gymnosperms. Here, we conducted comparative transcriptomic profiles at different stages of male and female cone development in Pinus halepensis. Our aim was to reveal transcription factor encoding genes involved in reproductive induction and development. For accurate developmental stage identification, histological analysis preceded the molecular analysis. The flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…In conifers, the function of FT gene is still controversial ( Klintenas et al., 2012 ). Studies have showed that FT plays a key role in the formation and growth of Norway spruce bud set, but is not involved in the induction of Pinus halepensis cone flowering induction, but is related to the vegetative bud dormancy ( Gyllenstrand et al., 2007 ; Reisfeld et al., 2022 ). In this study, transcriptome sequencing of male and female cones produced 71097 and 31195 DEGs, respectively, that were enriched in different cone flowering process pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In conifers, the function of FT gene is still controversial ( Klintenas et al., 2012 ). Studies have showed that FT plays a key role in the formation and growth of Norway spruce bud set, but is not involved in the induction of Pinus halepensis cone flowering induction, but is related to the vegetative bud dormancy ( Gyllenstrand et al., 2007 ; Reisfeld et al., 2022 ). In this study, transcriptome sequencing of male and female cones produced 71097 and 31195 DEGs, respectively, that were enriched in different cone flowering process pathways.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that studies on the molecular mechanisms of flower development are well established in angiosperms, while research into gymnosperms is relatively scarce [18,19]. In this Special Issue, a new publication compares the transcriptomic profiles of male and female Pinus halepensis cones at different developmental stages in order to uncover the genes involved in their reproductive induction and development [20]. The authors demonstrate that the expression of the C-class genes MADS1 and DAL14 correlate with female cone development, whereas male cone development is associated with the expression of the B-class genes PhDAL11 and PhDAL13 and the C-class gene PhMADS2.…”
mentioning
confidence: 99%